Netherlands Reports to the XIth International Congress of Comparative Law Caracas 1982
IX, 446 p.
Keywords: Last year I addressed the Netherlands Comparative Law Asso ciation with the following question: 'Does Comparative Law Exist At All?' (My intention then was to flog the dead (?) horse of the merger of comparative law and the sociology of law. ) In presenting this voluminous collection of Netherlands national reports to the eleventh congress of the Internatio nal Academy of Comparative Law I feel my misgivings giving way to the suspicion, that comparative law indeed exists. Of course national reports do not, as such, prove the exist ence of comparative law. It is the general reports together with the national reports, which embody the comparative effort. That is why the Netherlands Comparative Law Associa tion took the initiative to propose the publishing of the materials on a subject to subject basis instead of publish ing collections of national reports. From a comparative legal point of view, it is the topic that should form the basis of the publication, and not the origin of the materials. The general reporter for each topic should be prepared to take up the responsabilities of editing the volume, and would have to be given the right to select those national reports which he considers to be useful both in regard to their quality and the relevance of the material to the basic problems in the questionnaire. This proposal met with very favourable comments from the na tional committees and general reporters of some fifteen coun tries.